2021
DOI: 10.14202/vetworld.2021.926-932
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of peste des petits ruminants virus from goats in Egyptian governorates

Abstract: Background and Aim: The peste des petits ruminants (PPR) is a highly contagious disease of small ruminants which negatively affects animal production and the socioeconomic status of farmers. Peste des petits ruminants virus (PPRV) encodes eight proteins, with the viral fusion protein (F) playing a role in virus virulence and stimulating an effective protective immune response. This study aimed to isolate and complete the identification of PPRV circulating in goats in different Egyptian governorates and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In this study, PPRV strain was highly identical to isolates previously identified in Egypt (MG564286 PPR El-Kalubeya, JN202924 PPR Ismailia3/2010, JN202923 PPR Ismailia1/2010 and JX312807 PPR Ismailia2/2012) with a percentage of identity (100, 99.4, 99.1 and 95.5%), respectively. Consequent, this strain belonged to lineage IV as In the previous studies from different localities of Egypt (Sharawi and Abd-El-Rahim 2011;Soltan and Abd-Eldaim 2014;Ahmed et al 2021). This similarity between the Egyptian isolates may be associated with uncontrolled movement of sheep and goats within and between the governorates.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, PPRV strain was highly identical to isolates previously identified in Egypt (MG564286 PPR El-Kalubeya, JN202924 PPR Ismailia3/2010, JN202923 PPR Ismailia1/2010 and JX312807 PPR Ismailia2/2012) with a percentage of identity (100, 99.4, 99.1 and 95.5%), respectively. Consequent, this strain belonged to lineage IV as In the previous studies from different localities of Egypt (Sharawi and Abd-El-Rahim 2011;Soltan and Abd-Eldaim 2014;Ahmed et al 2021). This similarity between the Egyptian isolates may be associated with uncontrolled movement of sheep and goats within and between the governorates.…”
Section: Discussionsupporting
confidence: 51%
“…On the other hand, lineage IV has been found in a larger number of countries. Since its first detection in Israel in 1993 [ 35 ], its presence has been evidenced in Egypt 2012 [ 36 , 37 , 38 ], Iran [ 39 , 40 ], Iraq [ 41 ], Jordan [ 42 ], Kuwait [ 33 ], Palestine [ 43 ], the KSA [ 30 , 44 ] and the UAE [ 45 ]. No PPR sequences are available for Bahrain and Lebanon.…”
Section: Ppr Situation At the Regional Levelmentioning
confidence: 99%
“…In 2012, PPR outbreaks were documented in sheep flocks in the Ismailia and Cairo Governorates [ 17 , 36 ], leading to the development and application of a national strategy to control the disease. Subsequently, PPR has been reported annually ( Figure 5 ) and multiple studies have found considerable seroprevalence rates in unvaccinated SRs sampled in different governorates [ 37 , 38 , 54 , 55 , 56 ].…”
Section: Ppr Situation At the National Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…PPR infection was recorded in sheep flocks in the Giza governorate (Moatamadia village, Zenien, Saft El-Labn, and Kafrberak El-Khiam) ( Safwat, 2015 ). PPR has reappeared in some Egyptian governorates ( Mahmoud et al , 2017 ; Ahmed et al , 2021 ). PPR virus (PPRV) antibodies were detected in 63.7% of sheep and goats, in which goats were more sensitive to infection of the PPR virus than sheep, and the viral antigen detection increased in winter more than in other seasons.…”
Section: Introductionmentioning
confidence: 99%